A Green Internet of Things (GIoT) Adoption Framework to Enhance Environmental Performance of SMEs Through the Digital Social Networking - Muhammad Farhan, Jalil; Dayang Affizzah, Awang Marikan; Mohamad, Jais; Kartinah, Ayupp; Muhammad Hafiz, Mohd Shukri (John Wiley & Sons, Inc., 2025)
Small and Medium Enterprises (SMEs) face increasing pressure to adopt sustainable practices, yet the adoption of advancedtechnologies like the Green Internet of Things (GIoT) remains limited. This study addresses this gap by proposing and validatinga GIoT adoption framework aimed at enhancing environmental performance, emphasizing the mediating role of digital socialnetworking (DSN). Extending the Unified Theory of Acceptance and Use of Technology (UTAUT), the model incorporates per-ceived motivation and perceived environmental knowledge as additional predictors. A quantitative survey of 614 SME ownersand managers from manufacturing and service sectors was conducted, and structural equation modelling (SEM) was used foranalysis. Results show that all UTAUT constructs, along with the extended variables, significantly influence GIoT adoption.GIoT adoption directly improves environmental performance and promotes DSN, which further amplifies its positive environ-mental impact. The study also reveals that manufacturing SMEs exhibit a stronger intent to adopt GIoT. Implications for policyand practice are discussed.